Isolasi dan Karakterisasi Bakteri Penghasil Bioetanol dari Lingkungan Industri Arak di Desa Tri Eka Buana, Kecamatan Sidemen, Karangasem Bali - Bagaskara, Awang; Wijaya, I Made Mahaputra; Antara, Nyoman Semadi (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI, 2020)
This research aim ed to determine the ability of each bacterial isolate to produce ethanol, isolate and characterize bacteria that have the ability to produce potential ethanol from lau and air in the Arak Industry of environment in the Tri Eka Buana Village, Sidemen District, Karangasem Bali. Samples were obtained from 3 Hamlets in Tri Eka Buana Village . Bacteria were taken from l au before fermentation, during fermentation, and after fermentation. Bacteria from air were taken from the fermentation, distillation, and under the coconut tree and the variation of time is 15, 30, and 60 minutes of exposure . Bacteria from l au were isolated by growing on growth media, periodically (after 30, 60, 90, 120, and 150 seconds ) the isolates were taken from suspension to be inoculated in growth media for gas production . Isolation was carried out using YEPD-fluconazole media to obtain pure isolates. The fluconazole concentration used was 0 , 2 g/L. Pure isolates were then carried out qualitative tests for gas production and quantitative tests with alcohol oxidation reactions. The results of UV-Visible spectrophotometry , there were 6 best isolates and then fermented in YEPD media on a scale of 900 mL for 10 days. The fermentation results were then distilled using a reflux distilator. BU3 . 111E1 isolate s are determind the best isolates with 8,50% brix ethanol . The BU3.111E1 were obtained from air bacteria in Pungutan Hamlet , place of sampling during the fermentation process for 15 minutes. From the characterization results, isolate BU3.111E1 was Gram positive bacteria , basil bacteria , motile bacteria, and catalase negative. This study proved that the bacteria had the ability to produce ethanol. Keyword: isolation, bioethanol, arak, bacteria, UV-Visible spectrophotometry